What Price Social and Health Care? Commodities, Competition and Consumers - Sue Penna; Martin O'Brien (Social Work and Society, 2006)
This paper is concerned with actual and proposed changes affecting the organization and funding of health and social care services (HSCS), across the member states of the European Union. It focuses on some important disputes and problems surrounding the legal status and social purpose of HSCS through an examination of a Framework Directive on Services of General Interest (hereafter the Directive), adopted by the European Commission in 2004, which stalled within a quagmire of technical problems and political disputes, and eventually, following a vote in the European Parliament in February 2006, proceeded only by excluding health and social services from its provisions. These services are now the subject of further initiatives. It is worth noting here that the distinction between health services and social services has become increasingly blurred and, in the UK at least, the separation between social work and social care at a political and organizational level is becoming unclear, whilst at the same time both are becoming increasingly embedded in health services (see, for example, Department of Health 2006). In 2005, a move to integrate health and social care systems was announced by Care Services Minister, Liam Byrne. This move is concerned with both adult social care and all care received outside of hospitals. And more recently still, the British government announced plans to extend the marketization and commodification of health services (Department of Health 2006). This flurry of activity by the British government is paralleled in the European Union. It is this widespread interest with HSCS at the level of national and international policy that we wish to explore. We do this by mapping out policy processes in the institutions of the European Union (EU) currently affecting HSCS, and situating these within broader social developments. Specifically, the paper aims to illustrate the way in which the technical detail of the Directive and subsequent developments (European Commission 2006) are embedded within contradictory political projects. We concentrate on the Directive here as it formed the springboard for a significant and on-going struggle over the direction of societies that comprise the European Union.